Sierra Leone : 2008 Article IV Consultation, Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Financing Assurances Review, and Requests for Waivers of Nonobservance of Performance Criteria, Augmentation of Access, and Modification of Performance Criterion; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Sierra Leone. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2008 Article IV Consultation highlights that Sierra Leone's macroeconomic performance in 2008 was mixed. Output growth reached 6.4 percent in 2007, led by solid agricultural and mining production and buoyant activity in the construction and services sectors. The external current account deficit increased slightly in 2007 following a slight deterioration in the terms of trade. The authorities have made significant progress in implementing structural reforms in key areas. Growth prospects over the medium term remain encouraging with the expansion of available land for agriculture and intensification of extension services.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet